Anti-Bacterial Activities of Melastoma Malabathricum Stem Bark Fractions against Streptococcus Mutans - Rohazila Mohamad Hanafiah; Zurairah Ibrahim; Siti Aisyah Abd Ghafar; Wan Yaacob Wan Ahmad; Wan Syaidatul Aqma; Nazlina Ibrahim (Universiti Sains Islam Malaysia, 2024)
The objective of this study is to isolate and identify the bioactive compounds that possess antibacterial activities from Melastoma malabathricum stem bark acetone extract (MMSBAE) against Streptococcus mutans. M. malabathricum is widely used in the Southeast Asia to treat many ailments. A total of 12 fractions was purified by vacuum liquid chromatography (VLC) and further analysed by TLC-bioautography to determine antibacterial activities. TLC-bioautography showed that fraction 9 possesses antibacterial activities against S. mutans. Identification of fraction 9 had been done by GCMS and revealed 21 compounds. Some of the compound were important as agent pharmaceutical such as α-amyrin, β-sitosterol, hexadecenoic acid, stearic acid and hexacosanoic acid. Crystal violet and glass surface assay were used to determine anti-biofilm and anti-adherence activity, respectively. The concentrations of fraction 9 that produce 50% reduction in anti-biofilm and anti-adherence activities were 5 mg/mL and 2.50 mg/mL, respectively. Scanning electron microscopy (SEM) was performed to visualize the effect of the fraction 9 on biofilm structure of S. mutans. SEM analysis showed lysed biofilm were found on treated cells. These results indicated that this fraction possesses a powerful anti-cariogenic potential against S. mutans.